EDGES OF IMPROVING THE EFFICIENCY OF WIRELESS COMMUNICATION NETWORKS - Ismailov , Ma’murjon Mukhtarovich; Islamov , Asadbek (Educational Research in Universal Sciences, 2023)
At the same time that information technologies are rapidly developing, communication and information exchange are also developing at a great speed. Use communication tools to increase the ease of communication. These wires connected users with each other through communication centers and thus established communication between cities and countries. Nowadays, modern products of such wires are used. An example of these is fiber optic cables. It has several advantages. But even such fiber connections cannot meet the requirements of the time. Because this wire connection has several disadvantages related to it. Examples of these include pulling these wires to some communication centers, inconveniences in the placement of wires, etc. n addition, raw materials are used for making wires.